The Non-Foundational Epistemology of Nicholas Wolterstoff - Harsevoort , Stuart J. (My University, 2004)
Nicholas Wolterstorff, working within the context of Reformed Epistemology, has come to an understanding of knowledge which more accurately reflects the process of knowledge and belief that people experience than the foundational system to which he responds. He reacts to Immanuel Kant and John Locke, using arguments put forward by Thomas Reid, and building on these arguments with his own understanding.
Kant, Wolterstorff argues, had put distance between a person and what she could perceive about and attribute to God. Since she cannot have an experience of God, she experience5what Wolterstorff calls the 'Kantian agony'-she cannot discuss God without first discussing God's existence.
Locke, Wolterstorff argues, had put distance between a person and what she could believe. Locke, to whom Wolterstorff responds quite extensively, had argued that a person must use reason to govern her beliefs, and base her system of knowledge on propositions which can be known with certainty.
Reid responded to this system, which he called the 'theory of ideas', arguing that it entailed a skepticism about the world which no one could live by. He argued that people must assume things about the world, such as that it exists, in order to be able to live and work in it. Responding directly to the way that the way of ideas theorists understood perception.
Wolterstorff takes this understanding of perception and Reid's notion of belief-producing dispositions, and sets up a non-foundation account of knowledge which has room for religious faith. His system is a situational system, in which every person must govern their beliefs based on the system of beliefs in which they find themselves. This system, he argues more accurately reflects the way in which people come to knowledge, rather then the Kantian or Lockean (foundational) system.
Keywords: Nicholas Wolterstorff; Reformed Epistemololgy; Immanuel Kant; John Locke; perception; God